Role of insulin resistance and the gut microbiome on urine oxalate excretion in ob/ob mice - Hong Xiang; Haoqing Chen; Yuanyuan Liu; Dylan Dodd; Alan C. Pao (Physiological Reports, 2022)
Abstract Ob/ob mice have recently emerged as a model for obesity‐related hyperoxaluria as they are obese and excrete more urine oxalate compared to wild type mice. Ob/ob mice are deficient of leptin and develop obesity with hyperphagia and hyperinsulinemia. We hypothesized that insulin resistance and the gut microbiome contribute to hyperoxaluria in ob/ob mice. We developed a new liquid chromatography–mass spectrometry assay for urine oxalate and first compared urine oxalate excretion in ob/ob mice before and after ablation of intestinal bacteria with a standard antibiotic cocktail. We then compared urine oxalate excretion in ob/ob mice before and after leptin replacement or pioglitazone treatment, two maneuvers that reduce insulin resistance in ob/ob mice. Ob/ob mice excreted more oxalate into the urine in a 24‐h period compared to wild type mice, but antibiotic, leptin, or pioglitazone treatment did not change urine oxalate excretion in ob/ob mice. Unexpectedly, we found that when food intake was carefully matched between ob/ob and wild type mice, the amount of 24‐h urine oxalate excretion did not differ between the two mouse strains, suggesting that ob/ob mice excrete more urine oxalate because of hyperphagia. Since the level of urine oxalate excretion in wild type mice in our study was higher than those reported in prior studies, future work will be needed to standardize the measurement of urine oxalate and to define the range of urine oxalate excretion in wild type mice so that accurate and valid comparisons can be made between wild type mice and ob/ob mice or other mouse models.